Об одном направлении повышения стабильности уставки тока перегрузки автоматических выключателей - Терешин, Виктор Николаевич; Богданова, Людмила Евгеньевна (НТУ "ХПИ", 2008)
Рассмотрено влияние значения тока калибровки автоматических выключателей на стабильность уставки тока перегрузки и разработан метод бестоковой калибровки, позволяющий повысить стабильность уставки тока перегрузки.

Influence of automatic switch calibration current values on overload current setting stability is investigated. A current-free calibration method that allows increasing stability of the overload current setting is developed.
About one direction of stability increase of automatic switch overload current setting
Keywords: ток; перегрузки; выключатели; бестоковая калибровка; overload current setting stability; current-free calibration method; automatic switch